Data and the Aggregate Economy - Veldkamp, Laura; Chung, Cindy (Journal of Economic Literature, 2024)
Recent data technology innovations, such as artificial intelligence and machine learning, have transformed the production of knowledge and increased the importance of data. This review explores how data—digitized information—has been modeled within classic macroeconomic frameworks. It compares the economics of data to other concepts such as ideas, patents, and learning-by-doing. This paper also shows potential ways to model applications for data, including innovation, process optimization, and matching. Because this research area is nascent, much of the article is devoted to open questions and directions for future data economy research. (JEL C80, D21, D83, E23, E24, J23)